Physique traits of lightweight rowers and their relationship to competitive success - Slater, G. J.; Rice, A. J.; Mujika,I.; Hahn, A. G.; Sharpe, K.; Jenkin, D. G. (British Journal of Sports Medicine, 2005)
Objectives: Physique traits and their relationship to competitive success were assessed amongst lightweight rowers competing at the 2003 Australian Rowing Championships.